Sistem Pendukung Keputusan Pemilihan Sunscreen Untuk Remaja Menggunakan Kombinasi Metode SAW dan ROC - Yesi Handayani; Endang Lestari Ruskan (KLIK: Kajian Ilmiah Informatika dan Komputer, 2024)
Ultraviolet (UV) rays can negatively affect the skin and increase the risk of developing skin cancer especially if it occurs throughout childhood and adolescence. For teenagers, especially those who are often active outdoors, use of sunscreen is very important in order to avoid premature aging and various harmful effects of UV radiation. The use of inappropriate products will hamper the sunscreen's ability to protect skin thoroughly and may cause side effects such as acne or irritation. There are many types and brands of sunscreen products for each skin type, as well as various product criteria that are also considered by teenagers in choosing the best sunscreen product. Role of information technology can help the process of determining the best sunscreen products quickly and precisely, one of which is Decision Support System. The method used is ROC method to determine the weight value of criteria and sub-criteria, and SAW method to determine the final value in ranking alternatives. The data source of this research was obtained by distributing questionnaires to 103 respondents who were teenagers in Palembang City. This study uses 8 alternatives and 8 criteria, namely registered BPOM (C1), acne skin condition (C2), skin type suitability (C3), composition (C4), price (C5), weight (C6), weight suitability to price (C7), and texture (C8). Based on the ranking results, the highest preference value for oily skin type is 0.802, dry skin type is 0.782, normal skin type is 0.788, sensitive skin type is 0.790, and combination skin type is 0.788. All of these skin types have the same alternative with the highest preference value for each skin type, namely alternative A1 (Azarine Calm My Acne Sunscreen Moisturizer SPF 35 PA+++).